Different fracture risk profile in patients treated with anti-osteoporotic drugs in real-life - G. Adami (Reumatismo, 2020)
In this retrospective study, we intended to investigate the baseline fracture risk profile in patients who started treatment with different anti-osteoporotic medications. We analyzed retrospectively the fracture risk calculated with DeFRA, a validated FRAX derived tool, in women who started an anti-osteoporotic treatment from 2010 to 2017. We analyzed baseline data of 12,024 post-menopausal women aged over 50 years. Teriparatide initiators had a baseline 10-year risk of major osteoporotic fracture of 82.1% with a Standard Deviation (SD) of 66.5%. Denosumab initiators and zoledronic acid initiators had a greater 10-year baseline risk of fracture (54.3%, SD 46.5% and 47.0%, SD 42.0 respectively) than patients initiated on alendronate (24.9%, SD 34.6%) and patients initiated on risedronate (23.9%, SD 24.1%). Using DeFRA, a FRAX™ derived tool, we showed significantly different fracture risk profiles in women who were started on various therapeutic agents for the treatment of osteoporosis in routine clinical practice.